98.0k views
0 votes
Please help me with #1Please help me on my hw

Please help me with #1Please help me on my hw-example-1
User Ermin
by
5.0k points

1 Answer

6 votes

The given expression is,


(2x^2)^3

According to the law of exponents,


\begin{gathered} (xy)^m=x^my^m\text{ ---(a)} \\ (x^m)^n=x^(mn)\text{ ---(b)} \end{gathered}

Applying the law of exponents to the given expression,


\begin{gathered} (2x^2)^3=2^3(x^2)^3\text{ (using law (a))} \\ =8x^(2*3)\text{ (using law (b))} \\ =8x^6 \end{gathered}

Therefore, the correct expression is


(2x^2)^3=8x^6

User Godeke
by
5.3k points